2007
DOI: 10.3171/foc.2007.22.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lumbar spinal stenosis with a total posterior arthroplasty prosthesis: implant description, surgical technique, and a prospective report on 29 patients

Abstract: Object Total disc replacement is an alternative to lumbar fusion, but patients with spinal stenosis, spondylolisthesis, and facet arthropathy are often excluded from this procedure because increased adjacent-segment motion can exacerbate dorsal spondylotic changes. In such cases of degenerative spondylolisthesis with stenosis, decompression and fusion remain the gold standard of treatment. To avoid attendant loss of motion at the treated segment, the TOPS system is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…As well, the center of rotation for the segment shifts away from where it exists when the facet joints are intact. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, the center of rotation for the segment shifts away from where it exists when the facet joints are intact. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Considering the functional importance of facet joints, when removal of a facet is required, it is important to apply an implant that will simulate the role of the facet joint. The literature describes numerous pioneered systems[ 5 6 7 8 ] for total facet replacement, including TOPS, DSS, TFAS, and Stabilimax NZ; but none of these has yielded satisfactory clinical results worldwide. Moreover, surgical application of TOPS is reported to be difficult, and DSS and Stabilimax NZ are originally complex dynamic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently McAfee et al reported clinical improvement with a motionpreserving facet replacement system (TOPS). 28 …”
Section: Discussionmentioning
confidence: 99%
“…The TOPS System is an active singlelevel prosthesis wedged between two pedicle screw-fixated titanium plates. It allows for side bending, axial rotation, and flexion/extension range of motion while limiting sagittal translation [13]. It is currently indicated for LSS, spondylolisthesis, and facet arthrosis and has been increasingly proven safe and effective for these conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It allows for side bending, axial rotation, and flexion/extension range of motion while limiting sagittal translation [13]. It is currently indicated for LSS, spondylolisthesis, and facet arthrosis and has been increasingly proven safe and effective for these conditions [13][14][15]. Despite this encouraging evidence, it continues to be an experimental device and, thus, further high-quality studies are warranted.…”
Section: Introductionmentioning
confidence: 99%